An approach for developing compactness measurement indices in cotton (Gossypium spp.) - SANKARANARAYANAN, K; MANIVANNAN, A; PRAKASH, A H (The Indian Journal of Agricultural Sciences, 2021)
High density planting with compact genotypes proved, as high potential system of cotton cultivation. There is a need to develop proper indices to measure compactness in plant, is necessitated for screening of genotypes. Compactness measured using ((R× r) × √ h) was identified as an efficient method, based on that genotypes NSBT 108 , PAU1 , OUAT Bt 2 , CICR- K 34007 and CICR-CSH 19-2 were identified as compact genotypes. Compact Efficiency Index (CEI 1) was suitable for measuring efficiency of compactness.